2013
DOI: 10.1128/jcm.00087-13
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Human Papillomavirus Infections with High Viral Loads Are Associated with Cervical Lesions but Do Not Differentiate Grades of Cervical Abnormalities

Abstract: Multiple human papillomavirus (HPV) genotypes often coexist within cervical epithelia and are frequently detected together in smears of different grades of cervical neoplasia. Describing the association between multiple infections and cervical disease is important in generating hypotheses regarding its pathogenesis. We analyzed the prevalence of multiple HPV infections and their attribution to cervical disease in a screening population of 999 consecutive BD SurePath liquid-based cervical cytology samples enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
88
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 33 publications
9
88
2
4
Order By: Relevance
“…However, RT-PCR was used which has high sensitivity and allows small amounts of viral DNA to be detected, compared to other methods [13,18]. This has been previously demonstrated by studies carried out involving RT-PCR which have reported high multiple infection frequency [39,40]. Such differences regarding co-infection prevalence reported in various studies might have been due to their design, sample size, the HPV detection methods used and the population being studied (geographic, demographic and clinical factors) [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, RT-PCR was used which has high sensitivity and allows small amounts of viral DNA to be detected, compared to other methods [13,18]. This has been previously demonstrated by studies carried out involving RT-PCR which have reported high multiple infection frequency [39,40]. Such differences regarding co-infection prevalence reported in various studies might have been due to their design, sample size, the HPV detection methods used and the population being studied (geographic, demographic and clinical factors) [37].…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of single or co-infection with multiple HPV types has been found in sexually active adolescents, young women [3-7], and women with impaired immune responses [8]. …”
Section: Introductionmentioning
confidence: 99%
“…So, the cytological or pathologic finding was not helpful for the prediction of HPV existence in this study. HPV load and cumulative incidence of cervical lesion are known to be significantly correlated [15, 16]. At the view of guideline change, the position of HPV DNA test moves from the adjunctive test method to cotest method.…”
Section: Discussionmentioning
confidence: 99%